Normatively legal adjusting of the legal status of a child with the limited possibilities in Ukraine: historically legal aspect - Єрмілова, Марина Георгіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article deals with regulatory legal status of children with disabilities in Ukraine. We give a meaningfulanalysis of existing national legislation in this area, we study the provisions of international instrumentson this issueю\.